2007
DOI: 10.1258/002367707780378131
|View full text |Cite
|
Sign up to set email alerts
|

The antinociceptive efficacy of buprenorphine administered through the drinking water of rats

Abstract: SummaryPostoperative pain management in laboratory animals is important for animal welfare and required under law in many countries. Frequent injection of analgesics to rodents after surgery is stressful for the animals and labour-intensive for animal care personnel. An alternative dosing scheme such as administration of analgesics in the drinking water would be desirable. However, the efficacy of a chronic oral analgesic treatment via this route has not yet been documented. This study investigated the antinoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 19 publications
3
23
0
Order By: Relevance
“…We do not believe that prolonging the presurgical sucralose consumption period would have increased analgesic efficacy because previous studies have shown that 15 h of voluntary buprenorphine ingestion was required to reach similar or higher blood concentrations than subcutaneous administration 24 . Previous studies have suggested that the willingness of the animal to ingest water may enhance inter-subject variation 29 , but that does not apply here as there was comparable water Table 1. University of Toronto recommendations for dose, route and frequency of mouse analgesics following surgery.…”
Section: Discussionmentioning
confidence: 91%
“…We do not believe that prolonging the presurgical sucralose consumption period would have increased analgesic efficacy because previous studies have shown that 15 h of voluntary buprenorphine ingestion was required to reach similar or higher blood concentrations than subcutaneous administration 24 . Previous studies have suggested that the willingness of the animal to ingest water may enhance inter-subject variation 29 , but that does not apply here as there was comparable water Table 1. University of Toronto recommendations for dose, route and frequency of mouse analgesics following surgery.…”
Section: Discussionmentioning
confidence: 91%
“…Variations in analgesic efficacy, evaluated according to tail withdrawal latencies, have been noted among various strains of adult male rats 19. Intriguingly, repeated injected doses of 0.1 mg buprenorphine per kg body weight can elicit antinociceptive tolerance in male rats 20. In our study, we chose to administer buprenorphine s.c. every 12 h, as this administration frequency and route are common in US laboratory animal research protocols that use buprenorphine.…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we chose to administer buprenorphine s.c. every 12 h, as this administration frequency and route are common in US laboratory animal research protocols that use buprenorphine. Oral dosing of buprenorphine is complicated by changes in water consumption in the absence of operative procedures 20.…”
Section: Discussionmentioning
confidence: 99%
“…Strain and sex of rodents can also modulate response to opiates (Jablonski et al, 2001;Avsaroglu et al, 2007Avsaroglu et al, , 2008Cotroneo et al, 2012;Wright-Williams et al, 2013). Although usually given as an injection, in some studies orally administered buprenorphine was efficacious in alleviating postoperative pain, however, its utility may be limited in duration of analgesia and by reliable consumption of the food stuffs or water into which it is compounded (Flecknell et al, 1999a;Martin et al, 2001;Jablonski and Howden, 2002;Thompson et al, 2004Thompson et al, , 2006Jessen et al, 2007;Goldkuhl et al, 2010a,b;Leach et al, 2010b;Kalliokoski et al, 2011;Abelson et al, 2012). Additionally, sustained release and transdermal formulations of buprenorphine are emerging as potentially viable and practical opiate delivery systems (Park et al, 2008;Foley et al, 2011;Carbone et al, 2012a).…”
Section: A Opioidsmentioning
confidence: 99%